Causal Factors Affecting Strategic Change Management and Creating Shared Value of World-Class Standard Schools - Pansakan Phumsuwan; Chanyaphak Lalaeng (Journal of Posthumanism, 2025)
This research aims to check the consistency and develop a model. It also explores causal factors affecting Strategic Change Management and Creating Shared Value of World-Class Standard Schools. The population used in this study was 593 school administrators of international standard schools that received the OBECQA Quality Award, a sample of 340. Using the Smart PLS model, a two-stage approach was used for direct path, and mediation effect analysis with high-dimensional latent variables. The results of the study found that Creative Leadership (CL) positively influences Strategic Change Management (SCM), Proactive Human Resource Management (PHRM) positively influences Change Management (SCM), and Creating Shared Value (CSV), Stakeholder Engagement (SE) positively influences Change Management (SCM), and Creating Shared Value (CSV), in addition Change Management (SCM) positively influences Creating Shared Value (CSV). Indicating hypothesis H1, H3, H4, H5, H5, and H7 were deemed statistically significant, the hypothesis is supported. But Creative Leadership (CL) no influences Creating Shared Value (CSV). Indicating hypothesis H2 is not supported. However, Creative Leadership (CL), Proactive Human Resource Management (PHRM), and Stakeholder Engagement (SE) all positively influences Creating Shared Value (CSV) through the moderator of Change Management (SCM). Indicating hypothesis H7, H8, H9 were deemed statistically significant, the hypothesis is supported.
Keywords: Educational Systems and Policies; Education and Learning Interventions; Education, Safety, and Science Studies